2006
DOI: 10.1128/aac.50.5.1623-1627.2006
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Increase Antibiotic Susceptibility in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen. Treatment is complicated by frequent acquired resistance to antipseudomonal therapies. Polyamines (cadaverine, putrescine, spermidine, and spermine) are ubiquitous polycationic compounds essential for all living organisms. In a dose-dependent manner, polyamines increased the susceptibility of P. aeruginosa to 14 ␤-lactam antibiotics, chloramphenicol, nalidixic acid, and trimethoprim as demonstrated by a reduction in MIC of up to 64-fold. This effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 33 publications
10
77
0
Order By: Relevance
“…The MIC of antibiotics was determined by broth microdilution method according to the guidelines of the Clinical and Laboratory Standards Institute (47,48). Briefly, 96-well plates containing 2-fold dilution of antibiotics were prepared in Mueller-Hinton broth, and wells were inoculated with ϳ10 5 CFU/ml of overnight bacterial cultures.…”
Section: Methodsmentioning
confidence: 99%
“…The MIC of antibiotics was determined by broth microdilution method according to the guidelines of the Clinical and Laboratory Standards Institute (47,48). Briefly, 96-well plates containing 2-fold dilution of antibiotics were prepared in Mueller-Hinton broth, and wells were inoculated with ϳ10 5 CFU/ml of overnight bacterial cultures.…”
Section: Methodsmentioning
confidence: 99%
“…Two carbapenem resistant clinical isolates (A21 for OXA-23 positiveand H1 for OXA-24 positive) were confirmed as rifampicin susceptible (MIC 0.5 μg/mL) and used as donor strains for conjugative transfer of carbapenem resistance. Mating conditions for the donor and recipient strains were essentially identical as described previously [21] except for an extended-mating period (16 to 18 hours). The mating mixtures were spread on LB agar plates containing meropenem (5 μg/mL) or carbenicillin (100 μg/mL) and rifampicin (100 μg/mL).…”
Section: Construction Of Rifampicin Resistant a Baumannii Atcc 19606mentioning
confidence: 99%
“…However, other studies show that polyamines can sensitize E. coli, S. aureus, Salmonella and P. aeruginosa to most β-lactams effectively increasing susceptibility against these and other drugs (886,893). The reduction in MIC suggested that any possible decrease in permeability, caused by polyamine inhibition of porin transport, did not play a major role or was not enough of a factor to generate resistance against most β-lactams in those studies (886,893).…”
Section: Generation Of the Transposon Librarymentioning
confidence: 97%
“…This reduction in resistance was not linked to a decrease in expression of ampC or to disruption of the outer membrane as expected of polycationic ions which are known to be outer membrane disorganizers (886). Similarly, A. baumannii clinical and lab strains were shown to be more susceptible to the β-lactams aztreonam, carbenicillin, piperacillin and ticarcillin when treated with spermine and spermidine, but only a slight to moderate effect was observed against ceftazidime or meropenem (887).…”
Section: Generation Of the Transposon Librarymentioning
confidence: 99%
See 1 more Smart Citation